2001
DOI: 10.1093/pcp/pce179
|View full text |Cite
|
Sign up to set email alerts
|

Photosystem II Damage and Repair Cycle in the Green Alga Dunaliella salina: Involvement of a Chloroplast-Localized HSP70

Abstract: The involvement of HSP70B in the photosystem II damage and repair process in Dunaliella salina was investigated. A full-length cDNA of the D. salina hsp70B gene was cloned and sequenced. Expression patterns of the hsp70B gene were investigated upon shifting a D. salina culture from low-light to high-light growth conditions, designed to significantly accelerate the rate of PSII photodamage. Northern blot analyses and nuclear run-on transcription assays revealed a significant but transient induction of hsp70B ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 49 publications
3
52
0
Order By: Relevance
“…This hypothesis is consistent with the observation that V de-epoxidation occurs immediately upon photodamage, and Z accumulation occurs in parallel with the accumulation of photodamaged PSII reaction centers in the chloroplast thylakoids. A prompt disassembly of the PSII holocomplex (Melis, 1991;Aro et al, 1993) and formation of a PSII repair intermediate (Melis, 1999;Yokthongwattana et al, 2001) are known to follow photodamage. Highly photoactive tetrapyrrole pigments are released by the PSII D1/D2 reaction center in the course of reaction center disassembly and D1 degradation and replacement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This hypothesis is consistent with the observation that V de-epoxidation occurs immediately upon photodamage, and Z accumulation occurs in parallel with the accumulation of photodamaged PSII reaction centers in the chloroplast thylakoids. A prompt disassembly of the PSII holocomplex (Melis, 1991;Aro et al, 1993) and formation of a PSII repair intermediate (Melis, 1999;Yokthongwattana et al, 2001) are known to follow photodamage. Highly photoactive tetrapyrrole pigments are released by the PSII D1/D2 reaction center in the course of reaction center disassembly and D1 degradation and replacement.…”
Section: Discussionmentioning
confidence: 99%
“…SDS-PAGE analysis of the thylakoid membrane proteins was performed with samples loaded on an equal Chl basis, followed by western-blot analyses with specific polyclonal antibodies. Figure 3 shows western blots with specific polyclonal antibodies against the D1 reaction center protein of PSII (Kim et al, 1993) or against a 160-kD PSII repair intermediate (Kim et al, 1993;Melis and Nemson, 1995;Yokthongwattana et al, 2001). The 160-kD protein complex is known to contain a photodamaged but as yet undegraded D1 protein (Kim et al, 1993) and the D2 protein of the PSII reaction center (Melis and Nemson, 1995).…”
Section: Photo-inhibition Status As a Function Of Growth Irradiancementioning
confidence: 99%
See 1 more Smart Citation
“…It has, however, been suggested that a kind of chloroplast Hsp70 in Dunaliella salina plays some role in repairing damaged D1 or in stabilizing dissociated components of the PSII complex. 16) Therefore, Hsp70 in chloroplast or cyanobacteria might have specific functions in the photosynthetic machinery.…”
Section: Discussionmentioning
confidence: 99%
“…after injury by UV radiation) by reducing the inactivation of PSII and intensifying the recovery. The role of the stress proteins in the repair of the photodamaged PSII would be the stabilization of the core of PSII reaction centres (Yokthongwattana et al, 2001). In macroalgae, exposure to UV radiation in the laboratory has proved to be a factor inducing HSP70, which depends on the UV dose and species.…”
Section: Uv Radiationmentioning
confidence: 99%